Monitoring Poverty Over Time : Some Lessons from Cote d'Ivoire - Jones, Christine; Ye, Xiao (World Bank, Washington, DC, 2012)
This note explores some of the factors that need to be taken into account in designing surveys, and in comparing poverty indicators over time for effective poverty monitoring. Cote d'Ivoire presents a number of household surveys that should, in principle, allow monitoring changes in poverty over time, including household surveys conducted in 1993 and 1995. Problems of comparability are highlighted, as are issues in generating poverty data, in order to be compared reliably. Serious problems that arouse from four main sources were: estimates of input housing expenditure, the effects of seasonality on household expenditure patterns, the method used to estimate purchased food expenditure, and, the deficiencies of the consumer price index.